Rare earth metal monatomic loaded nitrogen-doped three-dimensional carbon carrier as well as preparation method and application thereof

The effective catalysis and adsorption of lithium polysulfide in lithium sulfur batteries through rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon support is achieved, which solves the problem of shuttle effect of lithium polysulfide intermediate products in lithium sulfur batteries and improves the battery ratio Capacity and cycle life.

CN119170790AActive Publication Date: 2024-12-20SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410933867.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2024-12-20
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

The soluble lithium polysulfide intermediate product generated by lithium-sulfur batteries during discharge in the organic electrolyte system will shuttle to the negative electrode side and react irreversibly with metal lithium, resulting in loss of active substances and failure of metal lithium negative electrodes, affecting battery capacity and cycling performance.

Method used

Using rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon support, the three-dimensional three-dimensional carbon skeleton structure formed by interleaving the first carbon nanosheet and the second conductive carbon, the rare earth metal single atoms form a stable coordination with the nitrogen element, improving the conductivity and ratio Surface area, used for bidirectional catalysis of sulfur and polysulfides in lithium sulfur batteries.

Benefits of technology

It realizes efficient adsorption and catalytic active sulfur conversion, inhibits the shuttle effect, improves the specific capacity and cycle life of lithium sulfur batteries, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170790A_ABST
    Figure CN119170790A_ABST
Patent Text Reader

Abstract

The invention relates to a rare earth metal monatomic loaded nitrogen-doped three-dimensional carbon carrier as well as a preparation method and application thereof. The rare earth metal monatomic loaded nitrogen-doped three-dimensional carbon carrier has a three-dimensional carbon skeleton structure formed by interweaving first carbon nanosheets and second conductive carbon, and in the three-dimensional carbon skeleton structure, the first carbon nanosheets are connected through the second conductive carbon; the three-dimensional carbon skeleton structure is doped with a nitrogen element; the rare earth metal monatomic is loaded on the nitrogen element and forms stable coordination with the nitrogen element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion secondary batteries, and in particular relates to a rare earth metal single atom loaded nitrogen-doped three-dimensional carbon carrier and a preparation method and application thereof. Background Art

[0002] With the rapid development of new energy technologies, portable electronic devices, power batteries and energy storage systems have an increasingly urgent need for high-performance energy storage batteries. Lithium-sulfur batteries have a high theoretical specific capacity (about 1675 mAhg -1 ), high energy density (about 2675Whkg -1 ), rich raw material sources, low cost, and environmental friendliness, have become one of the research hotspots of new energy storage batteries. However, during the discharge process of lithium-sulfur batteries in an organic electrolyte system, soluble lithium polysulfide intermediates will be generated, which will shuttle to the negative electrode side under the action of concentration gradient and electric field to undergo irreversible reaction with metallic lithium, resulting in loss of active substances and failure of the metallic lithium negative electrode, affecting the battery capacity and cycle performance, and greatly hindering the commercialization of lithium-sulfur batteries. Therefore, constructing a highly conductive positive electrode structure with efficient catalytic sites can achieve effective adsorption and catalysis of lithium polysulfide, promote rapid reaction kinetics of lithium-sulfur batteries, thereby effectively inhibiting the shuttle effect and achieving high specific capacity and long cycle life.

[0003] By designing and preparing highly polar materials as sulfur carriers, effective adsorption and catalytic conversion of sulfur and polysulfides can be achieved, such as transition metal oxides (M x O y ), nitride (M x N y ), sulfide (M x S y ), phosphide (M x P y ) and other technologies, which have played an important role in improving the performance of lithium-sulfur batteries. However, since this type of material has a relatively low specific surface area, in order to achieve a better catalytic effect, it accounts for a large proportion in the electrode and requires special structural design, which reduces the content of active substances to a certain extent and affects the energy density of the battery.

[0004] Single-atom catalysts are widely used in electrocatalysis and other fields due to their characteristics of nearly 100% atomic utilization efficiency, atomic-scale size structure and high catalytic activity. Among them, MN xThe main focus is on the design of single-atom catalytic structures with coordinated configurations (M = Fe, Co, Ni, Cu, Zn, etc.). In recent years, single-atom catalysts have also received extensive attention in lithium-sulfur batteries. For single-atom catalysts for positive electrode adsorption catalytic reactions, it is necessary to further optimize the structure and component design, improve the conductivity of the structure and the single-atom content, and deepen the understanding of single-atom catalysis, so as to achieve effective utilization of active substances and improve the overall performance of batteries.

[0005] Rare earth metal single atoms have rich electronic orbital characteristics and are used in lithium-sulfur batteries. Their orbital hybridization theory has a potential catalytic conversion effect on polysulfides. In order to realize the application of rare earth metal single atoms in lithium-sulfur batteries, it is necessary to develop a preparation method for a rare earth metal single atom catalyst loaded on a conductive carrier with high conductivity and high specific surface area, so as to effectively catalyze the bidirectional conversion of sulfur and sulfide in lithium-sulfur batteries, thereby obtaining high-performance lithium-sulfur batteries. Summary of the invention

[0006] In view of the above technical problems, the purpose of the present invention is to provide a rare earth metal single atom loaded nitrogen-doped three-dimensional carbon carrier and a preparation method thereof and application in lithium-sulfur batteries.

[0007] In a first aspect, the present invention provides a rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier, wherein the rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier has a three-dimensional carbon skeleton structure formed by interweaving a first carbon nanosheet and a second conductive carbon, wherein the first carbon nanosheets are connected by the second conductive carbon; The three-dimensional carbon skeleton structure is doped with nitrogen; The rare earth metal single atom is supported on the nitrogen element and forms a stable coordination therewith.

[0008] Preferably, the mass percentage of the rare earth metal single atom in the rare earth metal single atom catalyst-supported nitrogen-doped three-dimensional carbon carrier is 0.5 to 5 wt %, preferably 1 to 4 wt %.

[0009] Preferably, the specific surface area of ​​the rare earth metal single atom catalyst supported by nitrogen-doped three-dimensional carbon carrier is 400 to 800 m 2 g -1 , pore volume is 1.6~2.5cm 3 g -1 .

[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier, the preparation method comprising the following steps: (1) dispersing g-C3N4 and a second conductive carbon in a buffer solution to obtain a mixed dispersion, then adding dopamine hydrochloride to polymerize the g-C3N4 and the second conductive carbon on the surface to form polydopamine, and separating to obtain a rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier precursor powder; (2) Dispersing the rare earth metal single atom loaded nitrogen-doped three-dimensional carbon carrier precursor powder in water, adding rare earth metal nitrate to allow the polydopamine to adsorb rare earth metal ions, filtering, washing for the first time, and then freeze-drying, followed by high-temperature calcination, acid washing, a second washing and a second drying, to obtain the rare earth metal single atom loaded nitrogen-doped three-dimensional carbon carrier.

[0011] Preferably, the second conductive carbon is at least one of powders or dispersions of carbon nanotubes, conductive carbon black, mesoporous carbon, carbon nanofibers, and graphene oxide, preferably a dispersion of carbon nanotubes and graphene oxide.

[0012] Preferably, the mass ratio of the g-C3N4 to the second conductive carbon is 10-40:1, preferably 20-30:1; the mass ratio of the g-C3N4 to dopamine hydrochloride is 1:1-5, preferably 1:1-3.

[0013] Preferably, the rare earth metal nitrate is at least one of the nitrates or nitrate hydrates of Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu.

[0014] Preferably, the mass ratio of the g-C3N4 to the rare earth metal nitrate or nitrate hydrate is 5-0.9:1, preferably 5-1:1; The adsorption of rare earth metal ions by polydopamine is carried out under stirring at room temperature, and the stirring time at room temperature is 6-24 hours.

[0015] Preferably, the high-temperature calcination is carried out in an Ar / H2 mixed atmosphere, the calcination temperature is 700-1000°C, preferably 850-1000°C, the insulation time is 1-3h, and the heating rate is 1-5°C / min.

[0016] In a third aspect, the present invention provides a lithium-sulfur battery, comprising a sulfur positive electrode, a separator, an electrolyte and a metallic lithium negative electrode; wherein the sulfur positive electrode is a composite positive electrode material obtained by heat-treating the above-mentioned rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier and sulfur.

[0017] Beneficial Effects The preparation method of the rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier provided by the present invention is simple and easy, low-cost, has a rich pore structure and excellent conductivity, can effectively load active substances while improving reaction kinetics, and achieve high active substance utilization and comprehensive electrochemical performance; The method for preparing the rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier for lithium-sulfur batteries provided by the present invention is simple and universal, can be used to prepare catalysts composed of different types of rare earth metal single atoms or double single atoms and multiple single atoms, and is suitable for the quantitative preparation of lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 XRD diagrams of the carrier materials prepared in Examples 1-4 and Comparative Examples 1 and 4 of the present invention; Figure 2 TEM image of 3D CeSA-NC prepared in Example 1 of the present invention; Figure 3 This is a HAADF-STEM image of the 3D CeSA-NC prepared in Example 1 of the present invention; Figure 4 The XANES function curve and Fourier transform EXAFS function curve of the CeL3 edge of the 3D CeSA-NC prepared in Example 1 of the present invention; Figure 5 The battery cycle performance diagram of the carrier material prepared in Example 1 of the present invention and Comparative Example 1 as the positive electrode; Figure 6 The first cycle specific capacity-voltage diagram of a lithium-sulfur battery using the carrier materials prepared in Example 1 and Comparative Example 1 of the present invention as the positive electrode; Figure 7 This is a battery cycle performance diagram of the carrier material prepared in Comparative Example 4 of the present invention as the positive electrode. DETAILED DESCRIPTION

[0019] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0020] First, the present invention provides a rare earth metal single atom loaded nitrogen doped three-dimensional carbon carrier. The rare earth metal single atom loaded nitrogen doped three-dimensional carbon carrier has a three-dimensional carbon skeleton structure formed by interweaving a first carbon nanosheet and a second conductive carbon, in which the first carbon nanosheets are connected by the second conductive carbon; the three-dimensional carbon skeleton structure is doped with nitrogen; the rare earth metal single atom is loaded on the nitrogen and forms a stable coordination with the nitrogen. The connection between the first carbon nanosheet and the second conductive carbon is in the form of a localized physical "welding" point.

[0021] In some embodiments, the mass percentage of the rare earth metal single atom in the rare earth metal single atom catalyst-supported nitrogen-doped three-dimensional carbon support can be controlled to be 0.5-5wt%, preferably 1-4wt%. If the mass percentage of the rare earth metal single atom is lower than 0.5wt%, it cannot play an effective catalytic effect; if the mass percentage of the rare earth metal single atom is higher than 5wt%, it is easy to cause agglomeration, thereby failing to ensure the single atom state of the rare earth metal.

[0022] In some embodiments, the specific surface area of ​​the rare earth metal single atom catalyst supported by nitrogen-doped three-dimensional carbon support is 400 to 800 m 2 g -1 , pore volume is 1.6~2.5cm 3 g -1 .

[0023] Different from simple carbon accumulation, the first carbon nanosheets in the nitrogen-doped three-dimensional carbon carrier provided by the present invention are connected by a second conductive carbon, and the connection points are in the form of local "welding" points, which makes it easier for the overall material to transmit electrons and has excellent conductivity; at the same time, its high specific surface area can evenly load rare earth metal single atoms and can be used in lithium-sulfur batteries, effectively adsorbing and catalyzing the conversion of active sulfur, inhibiting the shuttle effect, and improving reaction kinetics.

[0024] The following is an exemplary description of the preparation method of the rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier provided by the present invention. The preparation method may include the following steps: (1) dispersing g-C3N4 and a second conductive carbon in a buffer solution to obtain a mixed dispersion, then adding dopamine hydrochloride to polymerize the g-C3N4 and the second conductive carbon on the surface to form polydopamine, and separating to obtain a rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier precursor powder; (2) Dispersing the rare earth metal single atom loaded nitrogen-doped three-dimensional carbon carrier precursor powder in water, adding rare earth metal nitrate to allow the polydopamine to adsorb rare earth metal ions, filtering, washing for the first time, and then freeze-drying, followed by high-temperature calcination, acid washing, a second washing and a second drying, to obtain the rare earth metal single atom loaded nitrogen-doped three-dimensional carbon carrier.

[0025] The present invention uses g-C3N4 as a soft template to promote the formation of nitrogen-doped three-dimensional carbon carriers. As an example, the g-C3N4 can be prepared by heating urea as a raw material to 550° C. in a muffle furnace and keeping the temperature for 2 hours. The g-C3N4 is a yellow g-C3N4 powder.

[0026] The second conductive carbon is used as a conductive agent. In some embodiments, the second conductive carbon can be at least one of a powder or dispersion of carbon nanotubes (including surface functionalized carbon nanotubes), conductive carbon black, mesoporous carbon, carbon nanofibers, and graphene oxide, preferably a dispersion of carbon nanotubes and graphene oxide.

[0027] In some embodiments, the mass ratio of the g-C3N4 to the second conductive carbon can be 10-40: 1, preferably 20-30: 1. The g-C3N4 acts as a soft template to load the dopamine hydrochloride. The dopamine hydrochloride is coated on the g-C3N4 and then sintered to form a first carbon nanosheet. The volume of the nanosheet is much larger than that of the second conductive carbon such as carbon fiber. By controlling the mass ratio range of the two, an excellent three-dimensional structure can be formed. Too much or too little will affect the specific surface area and other properties of the material.

[0028] In some embodiments, the buffer solution may be a Tris-buffer solution.

[0029] In some embodiments, the mass ratio of g-C3N4 to dopamine hydrochloride can be 1: 1-5, preferably 1: 1-3. By controlling the appropriate mass ratio of the two, an effective coating effect can be ensured. Too much dopamine hydrochloride will cause waste, and too little dopamine hydrochloride will not achieve the best template effect of g-C3N4.

[0030] In some embodiments, dopamine hydrochloride is polymerized on the surface of g-C3N4 and the second conductive carbon to form polydopamine by stirring polymerization, and the reaction time may be 3-12 hours, preferably 3-8 hours.

[0031] In some embodiments, the rare earth metal nitrate can be at least one of the nitrates or nitrate hydrates of Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu.

[0032] In some embodiments, the mass ratio of g-C3N4 to rare earth metal nitrate or nitrate hydrate can be 5-0.9: 1, preferably 5-1: 1. Too much rare earth metal nitrate can easily lead to agglomeration and failure to form single atoms; too little rare earth metal nitrate can lead to too low single atom content.

[0033] In some embodiments, the adsorption of rare earth metal ions by polydopamine can be carried out under stirring at room temperature, and the stirring time at room temperature can be 6-24 hours.

[0034] The drying method will affect the uniformity of single atoms in the material. Freeze-drying can promote more uniform preparation of single atoms, while direct vacuum heat drying is prone to agglomeration, hindering the formation of single atoms.

[0035] High temperature calcination can stabilize the structure and form single atoms. In some embodiments, the high temperature calcination can be carried out in an Ar / H2 (5% H2) mixed atmosphere, the calcination temperature can be 700-1000°C, preferably 850-1000°C, the insulation time can be 1-3h, and the heating rate can be 1-5°C / min. If the calcination temperature is too low, incomplete carbonization will result; if the calcination temperature is too high, partial volatilization and side reactions will occur.

[0036] By using acid washing, uncoordinated metal or metal oxide impurities can be dissolved.

[0037] During the preparation process, the order of sample addition, drying method, and material content ratio are all related to the conductivity of the final material, the uniformity and content of the rare earth metal single atom distribution, and whether it can play an efficient catalytic effect. Different sample addition orders will affect the formation of local "welding" points, and then affect the conductivity. Adding g-C3N4 and the second conductive carbon first, and then adding dopamine is conducive to the formation of welding points; adding dopamine directly after adding g-C3N4 and then adding the second conductive carbon is not conducive to the formation of welding points. The material content ratio will affect the content of the prepared rare earth metal single atoms, which will directly affect the material's adsorption and catalytic active sulfur ability in lithium-sulfur batteries. The material content ratio is equivalent to the amount of rare earth metal nitrate used. Too much is easy to agglomerate and cannot form single atoms. Too little is used and the single atom content is low, which will lead to weakened material adsorption and catalytic ability.

[0038] The rare earth metal single atom catalyst provided by the present invention supports nitrogen-doped three-dimensional carbon as a sulfur carrier, has high conductivity, can effectively adsorb and catalyze the bidirectional conversion of reaction intermediate lithium polysulfide, and has excellent redox reaction kinetics; moreover, the composite carrier material provided by the present invention has a simple preparation process, excellent catalytic performance, and is suitable for high-performance lithium-sulfur batteries.

[0039] The present invention also provides a lithium-sulfur battery, comprising: a sulfur positive electrode, a separator, an electrolyte and a metallic lithium negative electrode; wherein the sulfur positive electrode is a composite positive electrode material obtained by heat-treating the above-mentioned rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier and sulfur.

[0040] As an example, the preparation method of the sulfur positive electrode may include the following steps: after uniformly mixing the rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier with sulfur, vacuum sealing it in a quartz tube and keeping it at 155°C for 12 hours, then heating it to 300°C and keeping it for 2 hours, uniformly mixing the obtained powder with conductive carbon and a binder, and coating it on the surface of an aluminum foil, and vacuum drying it to obtain the sulfur positive electrode.

[0041] In some embodiments, the separator used for assembling the battery in the lithium-sulfur battery can be a commercial porous polymer separator, and the electrolyte can be formed by dissolving 1M LiTFSI and 0.2M LiNO3 in a mixed solution of DOL / DME (volume ratio 1:1); wherein the lithium-sulfur battery is assembled in an argon glove box (water and oxygen contents are both less than 0.1ppm).

[0042] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values ​​​​exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0043] Unless otherwise specified, the prepared carrier material in the present invention is used as the positive electrode of a lithium-sulfur battery to perform constant current charge and discharge tests and cycle performance characterization on the battery at room temperature (25° C.), with a voltage range of 1.8-2.8V and a rate of 0.2C.

[0044] Example 1

[0045] The method for preparing the rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier provided in this embodiment comprises the following steps: (1) Weigh 0.9691 g of tris(hydroxymethyl)aminomethane hydrochloride) and dissolve it in deionized water to prepare 800 mL of 10 mM Tris-buffer solution; add 0.4 g of g-C3N4 and 0.15 g of carbon nanotube (CNT) dispersion (wherein the carbon nanotube content is 10 wt%) to the above Tris-buffer buffer, ultrasonically obtain a uniform dispersion, add 0.8 g of dopamine hydrochloride under stirring, stir at room temperature for 3 h, filter and wash with deionized water to obtain PDA@g-C3N4-CNT composite (rare earth metal single atom loaded nitrogen doped three-dimensional carbon carrier precursor powder); (2) The PDA@g-C3N4-CNT material obtained above was dispersed again in 300 mL of deionized water to obtain a uniform dispersion solution, and then 0.4330 g of Ce(NO3)3·6H2O was added and stirred at room temperature for 12 h to allow Ce to 3+ The precipitate was fully adsorbed on the nitrogen sites on the PDA surface, vacuum filtered and repeatedly washed with deionized water, and the filter cake was freeze-dried to obtain Ce 3+ -PDA@g-C3N4-CNT powder; react at 1000℃ for 1h in Ar / H2 (5% H2) mixed atmosphere with a heating rate of 2℃ / min. The cooled powder sample was placed in a 1M hydrochloric acid solution and stirred at room temperature for 6h to remove uncoordinated metals or metal oxides. Then, it was washed and dried to obtain a nitrogen-doped three-dimensional porous carbon support (3D CeSA-NC) loaded with a single Ce atom.

[0046] The 3D CeSA-NC prepared in Example 1 was heat-treated with sulfur to obtain a composite positive electrode material, which was then prepared into a battery for electrochemical performance testing.

[0047] Example 2

[0048] The preparation method of the rare earth metal single atom loaded nitrogen-doped three-dimensional carbon carrier provided in this embodiment refers to Example 1, with the main difference that the second conductive carbon is graphene oxide and the added amount of Ce(NO3)3·6H2O is 0.2165g.

[0049] Example 3

[0050] The preparation method of the rare earth metal single atom loaded nitrogen-doped three-dimensional carbon support provided in this embodiment refers to Example 1, with the main difference that the rare earth metal nitrate is La(NO3)3·6H2O, the high-temperature calcination time is 2h, and the obtained La single atom loaded nitrogen-doped three-dimensional porous carbon support (3D LaSA-NC) is obtained.

[0051] Example 4

[0052] The preparation method of the rare earth metal single atom loaded nitrogen-doped three-dimensional carbon support provided in this embodiment refers to Example 1, with the main difference that the rare earth metal nitrate is Sm(NO3)3·6H2O, the added amount is 0.4440 g, the stirring time at room temperature is 8 hours, and the obtained Sm single atom loaded nitrogen-doped three-dimensional porous carbon support (3D SmSA-NC) is obtained.

[0053] Comparative Example 1

[0054] The preparation method of the carrier material provided in this comparative example refers to Example 1, with the main difference being that the PDA@g-C3N4-CNT composite is directly calcined at high temperature to obtain a nitrogen-doped three-dimensional porous carbon carrier, denoted as 3D NC.

[0055] The 3D-NC prepared in Comparative Example 1 was heat-treated with sulfur to obtain a composite positive electrode material, which was then prepared into a battery for electrochemical performance testing.

[0056] Comparative Example 2

[0057] The preparation method of the carrier material provided in this comparative example refers to comparative example 1, with the main difference being that the order of adding the carbon nanotube (CNTs) dispersion is different. First, 0.4 g of g-C3N4 and 0.8 g of dopamine hydrochloride are added to Tris-buffer buffer and dispersed evenly to obtain a PDA@g-C3N4 composite solution. Then, 0.15 g of carbon nanotube (CNT) dispersion is added under stirring, and the mixture is stirred at room temperature for 3 h. After filtration, the mixture is washed with deionized water to obtain a PDA@g-C3N4-CNT complex.

[0058] The 3D NC prepared by this method does not have stable local "welding" points, and the first carbon nanosheets and the second conductive carbon are physically stacked, and the conductivity is weaker than the nitrogen-doped three-dimensional porous carbon structure described in Comparative Example 1.

[0059] Comparative Example 3

[0060] The preparation method of the carrier material provided in this comparative example refers to that of Example 1, with the main difference being that in step (2), the filter cake is dried by vacuum thermal drying.

[0061] The 3D CeSA-NC prepared by this method still exhibits agglomeration even after acid treatment, which is caused by direct vacuum drying.

[0062] Comparative Example 4

[0063] The preparation method of the carrier material provided in this comparative example refers to Example 1, with the main difference that: in step (2), the rare earth metal nitrate is replaced with 0.4039 g Fe(NO3)3·9H2O to obtain a nitrogen-doped three-dimensional porous carbon carrier (3D FeSA-NC) loaded with 3d transition metal Fe single atoms.

[0064] Figure 1 The XRD diagrams of the carrier materials prepared in Examples 1-4 and Comparative Examples 1 and 4 of the present invention are shown in FIG. As can be seen from the figure, the carrier materials prepared in Examples 1-4 belong to the graphite carbon (002) crystal plane and (101) crystal plane, and have no characteristic peaks of Ce, La or Sm metal phases, indicating that Ce, La or Sm exist in a single atomic form, and the Ce single atom content is 2.23% and 1.36% respectively; the carrier material prepared in Comparative Example 1 belongs to the graphite carbon (002) crystal plane and (101) crystal plane; the carrier material prepared in Comparative Example 4 belongs to the graphite carbon (002) crystal plane and (101) crystal plane, and has no characteristic peaks of Fe metal phases.

[0065] Figure 2 This is a TEM image of the 3D CeSA-NC prepared in Example 1 of the present invention. As can be seen from the image, the carrier material prepared in Example 1 presents a three-dimensional structure in which carbon nanotubes and carbon nanosheets are interwoven.

[0066] Figure 3 This is the HAADF-STEM image of the 3D CeSA-NC prepared in Example 1 of the present invention. As can be seen from the figure, there are obvious bright spots corresponding to Ce single atoms (CeSAs) in the material, proving the successful preparation of CeSAs.

[0067] Figure 4 The XANES function curve and Fourier transform EXAFS function curve of the CeL3 edge of the 3D CeSA-NC prepared in Example 1 of the present invention are shown in FIG. As can be seen from the figure, the metal Ce loaded in the product prepared in Example 1 of the present invention exists in the form of single atoms.

[0068] Figure 5 The battery cycle performance diagram of the carrier materials prepared in Example 1 of the present invention and Comparative Example 1 as positive electrodes. It can be seen from the figure that the carrier material prepared in Example 1 has a battery first discharge capacity of 1225 mAh g at 0.2C. -1 , much higher than the 1130mAh g in Comparative Example 1 -1 and 1089 mAh g of Comparative Example 4 -1 After 160 cycles, the capacity retention rate was 76.1%, indicating that Ce single atoms effectively accelerated the reaction kinetics and the performance was far superior to that of 3d transition metal single atom catalysts.

[0069] Figure 6 The first cycle specific capacity-voltage diagram of the lithium-sulfur battery with the carrier material prepared in Example 1 of the present invention and Comparative Example 1 as the positive electrode. As can be seen from the figure, the battery charge and discharge curve of the carrier material prepared in Example 1 as the positive electrode maintains the standard curve of the lithium-sulfur battery, and has a higher discharge specific capacity than the comparative sample, indicating the effectiveness of Ce single atom in the bidirectional catalytic process.

[0070] Figure 7 The figure is a battery cycle performance diagram of the carrier material prepared in comparative example 4 of the present invention as the positive electrode. It can be seen from the figure that the first discharge capacity of the battery at 0.2C reaches 1089 mAh g -1 After 160 cycles, the capacity retention rate was 67.8%.

[0071] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier, characterized in that: The rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier has a three-dimensional carbon skeleton structure formed by interweaving a first carbon nanosheet and a second conductive carbon, in which the first carbon nanosheets are connected by the second conductive carbon; The three-dimensional carbon skeleton structure is doped with nitrogen; The rare earth metal single atom is supported on the nitrogen element and forms a stable coordination therewith.

2. The rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier according to claim 1, characterized in that: The mass percentage of the rare earth metal single atom in the rare earth metal single atom catalyst-supported nitrogen-doped three-dimensional carbon carrier is 0.5 to 5 wt %, preferably 1 to 4 wt %.

3. The rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier according to claim 1 or 2, characterized in that: The specific surface area of ​​the rare earth metal single atom catalyst supported by nitrogen-doped three-dimensional carbon carrier is 400 to 800 m 2 g -1 , pore volume is 1.6~2.5cm 3 g -1 .

4. A method for preparing a rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) dispersing g-C3N4 and a second conductive carbon in a buffer solution to obtain a mixed dispersion, then adding dopamine hydrochloride to polymerize the g-C3N4 and the second conductive carbon on the surface to form polydopamine, and separating to obtain a rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier precursor powder; (2) Dispersing the rare earth metal single atom loaded nitrogen-doped three-dimensional carbon carrier precursor powder in water, adding rare earth metal nitrate to allow the polydopamine to adsorb rare earth metal ions, filtering, washing for the first time, and then freeze-drying, followed by high-temperature calcination, acid washing, a second washing and a second drying, to obtain the rare earth metal single atom loaded nitrogen-doped three-dimensional carbon carrier.

5. The preparation method according to claim 4, characterized in that: The second conductive carbon is at least one of carbon nanotubes, conductive carbon black, mesoporous carbon, carbon nanofibers, and graphene oxide powder or dispersion, preferably a dispersion of carbon nanotubes and graphene oxide.

6. The preparation method according to claim 4 or 5, characterized in that: The mass ratio of the g-C3N4 to the second conductive carbon is 10-40:1, preferably 20-30:1; the mass ratio of the g-C3N4 to dopamine hydrochloride is 1:1-5, preferably 1:1-3.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The rare earth metal nitrate is at least one of the nitrates or nitrate hydrates of Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The mass ratio of g-C3N4 to rare earth metal nitrate or nitrate hydrate is 5-0.9:1, preferably 5-1:1; The adsorption of rare earth metal ions by polydopamine is carried out under stirring at room temperature, and the stirring time at room temperature is 6-24 hours.

9. The preparation method according to any one of claims 4 to 8, characterized in that The high-temperature calcination is carried out in an Ar / H2 mixed atmosphere, the calcination temperature is 700-1000°C, preferably 850-1000°C, the insulation time is 1-3h, and the heating rate is 1-5°C / min.

10. A lithium-sulfur battery, characterized in that: The lithium-sulfur battery comprises a sulfur positive electrode, a separator, an electrolyte and a metallic lithium negative electrode; The sulfur positive electrode is a composite positive electrode material obtained by heat-treating and compounding the rare earth metal single atom-loaded nitrogen-doped three-dimensional carbon carrier according to any one of claims 1 to 3 with sulfur.

Citation Information

Patent Citations

  • Preparation method of carbon-covered sodium-ion battery positive electrode material

    CN107248574A

  • Nitrogen-doped ultra-thin carbon nanosheet loaded monoatomic catalyst and preparation method and application thereof

    CN109939717A

  • Preparation method of nitrogen-doped three-dimensional porous carbon loaded with nano cobalt and application thereof in lithium sulfur batteries

    CN110336032A

  • Rare earth monatomic modified nitrogen-doped porous carbon catalyst for lithium-sulfur battery and preparation method of rare earth monatomic modified nitrogen-doped porous carbon catalyst

    CN117154094A

  • Nanoporous metal-carbon composite

    US20160101398A1